Curtain Grouting To Reduce Seepage Foundation Access Road To The Top Of The Dam At Tugu Dam - Supriono Supriono; Agata Iwan Candra; Yosef Cahyo Setianto Poernomo; Mochammad Danara Indra Pradigta (U Karst, 2022)
The construction of a complementary access road to the top of the dam is to the left of the Tugu dam pedestal. Based on geological studies, it is feared that there is a potential for seepage that passes through the left pedestal through joints, fractures, and fault areas/rock layers below the foundation surface. To anticipate this, the allowable seepage requirement is the lugeon value (Lu) < 3. This study aims to determine the geological conditions and the amount of seepage before and after foundation repairs are carried out using the grouting method. The type of this research is field research, qualitative descriptive because this research tries to collect lugeon population and cement material absorbed into the rock from water pressure test and grouting injection work by grouping each type of hole, pilot hole, primary hole, secondary hole, tertiary hole, and check hole. The study results by taking rock cores found that the constituent rocks were volcanic breccia units and colluvial rocks. Furthermore, a water pressure test before grouting with a water passing value of (k) = 6.62E-05 to 4.73E-04 cm/sec or with a lugeon value (Lu) of 5.07 to 36.21. After repairing the foundation using rim curtain grouting, the seepage that occurs decreases with a water passing value (k) = 1.96E-05 to 3.03E-05 cm/sec or lugeon (Lu) 1.50 to 2.32, so the requirements the target value of Lu < 3 was achieved with the effectiveness in the good category.